Implementation Case Based Reasoning In Determining The Rational Prescription Of TB Drugs - Ahmad Cucus (Bandar Lampung University (UBL), 2014)
Case Based Reasoning has been widely applied in many artificial intelligence, expert systems and well shaped decision support systems that help decision-makers to take the right decisions. The use of CBR to diagnose the disease have also been made by several previous researchers. Yet another problem arises, namely the use of drugs that are not rational.